Hydrothermal growth of Zn2GeO4 nanorods for optical and (Photo)Catalytic applications: An experimental and theoretical study - Conti, Mary Carmen Maté Durek de; Camargo, Luan Pereira; da Silva Fabris, Guilherme [UNESP]; Catarini da Silva, Paulo Rogério; de Santana, Henrique; Fernandes, Ricardo Vignoto; Dall'Antonia, Luiz Henrique; Vandresen, Fábio; Sambrano, Julio Ricardo [UNESP]; La Porta, Felipe de Almeida (Elsevier, 2024)
From the material design perspective, we reported a systematic investigation based on theoretical and experimental approaches to explore the physical properties of Zn2GeO4 nanorods prepared by hydrothermal method with different zinc precursors for optical and (photo)catalytic applications. All ZGO samples exhibited uniform nanorod morphology with high purity and crystallinity. A negative zeta potential ranging from −13 mV to −16 mV have been observed for these nanorods. Bandgap values indicated variations among samples synthesized with different precursors. The photoluminescence and photocatalytic activities for these nanorods, have been attributed to the presence of oxygen vacancies on the Zn2GeO4 surfaces. Experimental evidence suggests that these surface defects favor the formation of hydroxyl radicals identified as primary reactive oxygen species responsible for the methylene blue photodegradation. Toxicity testing of photocatalytic residues showed minimal phytotoxic effect on lettuce seed (Lactuca sativa) germination. Additionally, Zn2GeO4 was utilized as an acid catalyst for synthesizing isoxazol-5(4H)-ones, resulting in an increase in the yield from 69 % to 92 % by using this catalyst in multicomponent reactions. Lastly, the theoretical efforts outlined in the study aim to enhance the comprehension of the material design with well-defined morphology using realist theoretical models for the Zn2GeO4 nanorods for the first time.
Keywords: DFT calculations; Hydrothermal synthesis; Nanorods; Optical and (photo)catalyst applications; Wide-bandgap semiconductor; Zn2GeO4